Designing elite football programmes that produce quality athletes and future ready adults: incorporating social emotional learning and career development - Blake, M.; Solberg, V. S. H. (Soccer & Society, 2023)
This article uses a positive youth development (PYD) perspective to recommend a number of programme design strategies for improving the mental health and wellbeing, future readiness, and performance of elite youth footballers in the academy system. Elite youth footballers refers to the estimated 12,000 boys (aged 8-21) who are contracted to professional academies at any one time, with many of these youth experiencing negative outcomes during their time within the academy system and beyond (e.g. psychological distress, inferior academic outcomes, academic disengagement, foreclosed identities, impaired social and emotional development). The recommendations are framed around key PYD competencies with the primary goal being to increase resilience, proactivity, and adaptability amongst these youth.